The Analysis of Learning Styles and Their Relationship to Academic Achievement in Medical Students of Basic Sciences Program - Reza Ghaffari; Fariba Salek Ranjbarzadeh; Eskandar Fathi Azar; Susan Hassanzadeh; Naser Safaei; Parisa Golanbar; Hossein Mazouchian; Elham Abbasi (Tabriz University of Medical Sciences, 2013)
Introduction: Learning style is an individual's preferred method of encountering information in specific situations in order to acquire knowledge, skills and attitudes through study or experience. Students and Planers' awareness of learning styles facilitate the teaching process, increases satisfaction and makes the future choices easier. This study aimed to examine different learning styles and their relation to academic achievement in medical students of basic sciences program at Tabriz University of Medical Sciences. Methods: In this descriptive - analytical study, the sample consisted of all medical students of basic sciences program at Tabriz University of Medical Sciences in 2011-2012. The data was collected through a questionnaire which included respondents' demographic information and overall grade point average (GPA) as well as Kolb standard questions on learning styles. Results: 4.3%, 47.8%, 44.9% and 2.9% of students preferred diverger, assimilator, converger and accommodator learning styles, respectively. Mean overall GPA of students who preferred diverger learning styles was 14.990.39±. Students who prefer assimilator, converger and accommodator learning styles had mean overall GPAs of 14.940.56±, 15.080.58± and 14.830.29± respectively. The findings showed no significant relationship between students' learning academic achievement and their learning styles (p = 0.689). Conclusion: There was no significant relationship between Students' academic achievement and their learning styles. Furthermore, the majorit of the students preferred accommodator and converger learning styles. Consequently, adopting interactive teaching methods, using tutorials, running simulation programs, launching laboratory activities and encouraging students to think and analyze problems and issues can be greatly effective in prolonging their learning lifecycle.